On the approaches to cyber-physical systems simulation - Shkarupylo, Vadym; Kudermetov, Ravil; Polska, Olga (Lviv Politechnic Publishing House, 2018)
A comparative analysis of existing approaches to Cyber-Physical Systems simulation has been conducted. The intrinsic peculiarities of Cyber-Physical Systems have been reasoned and generalized. The limitations of available simulation tools have been pointed out. The approach to Cyber-Physical Systems design solutions checking on the basis of timed automata, UPPAAL integrated tool environment and Temporal Logic of Actions usage has been proposed. The proposed approach is supposed to be applied at designing stage – to prevent the potential time and computational expenses on overcomplicated or faulty formal models checking. A case study on electric power delivery system usage scenario has been conducted.
Keywords: Cyber-Physical System; Model; Model Checking; Simulation; TLA; UPPAAL; Verification